Award to San Luis Obispo Buddhist Church from U.S. Department of Justice, Civil Division, for Evacuation Claims - Department of Justice, Civil Division::::::::: (1957)
Statement of the Evacuation Claims Compromise Settlement for the San Luis Obispo Buddhist Church from the United States Department of Justice, Civil Division. As stated in the award: "Pursuant to the Act of July 2, 1948 (62 Stat. 1231), as amended by Public Law 673, 84th Cong., the above-named claimant is hereby awarded the sum of One Thousand Two Hundred Seventy Dollars and No Cents ($1,270.00), in compromise settlement of the above-numbered claim. GEORGE COCHRAN DOUB, Assistant Attorney General, Civil Division. By: John T. Allen, Attorney in Charge, Los Angeles Office, Japanese Claims Section." Letter is cc'ed to Saburo Kido, Esq., 305 E. 2d Street, Los Angeles 12, Cal.